2020
DOI: 10.1016/j.jenvman.2020.110928
|View full text |Cite
|
Sign up to set email alerts
|

Implementing adaptive management into a climate change adaptation strategy for a drowning New England salt marsh

Abstract: Implementing adaptive management into a climate change adaptation strategy for a drowning New England salt marsh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Adaptive management can be an essential component of successful restoration projects (Buchsbaum and Wigand, 2012;Perry et al, 2020), but to what extent did adaptive management activities of the landscape and hydrology facilitate some of the outcomes documented after sediment placement in this study? We observed, but did not directly quantify, some apparent benefits (Supplementary Figure S4).…”
Section: Adaptive Managementmentioning
confidence: 97%
“…Adaptive management can be an essential component of successful restoration projects (Buchsbaum and Wigand, 2012;Perry et al, 2020), but to what extent did adaptive management activities of the landscape and hydrology facilitate some of the outcomes documented after sediment placement in this study? We observed, but did not directly quantify, some apparent benefits (Supplementary Figure S4).…”
Section: Adaptive Managementmentioning
confidence: 97%
“…Perry et al's 44 study of implicit Soft OR use in the development of coastal resource management planning in the eastern United States provides a good example of these kinds of efforts and illustrates some of the advantages to the government of implicit rather than explicit use. The team noted that maintaining stakeholder interests and commitment was an issue and acknowledged that the large funding required for their methodology can make its applications 'a significant challenge' .…”
Section: The Bristol Casementioning
confidence: 99%
“…Third, we need to forecast our process under these future climate scenarios. Then, as the fourth step, we can work towards mitigating impacts, preferentially through an adaptive management framework [ 15 , 16 ]. Robust ecological and temperature data are essential cornerstones of this process.…”
Section: Introductionmentioning
confidence: 99%